Application of Internet of Things (IoT) Technology in Agro-Industrial Supply Chain Management - Tri Waluyo (SEAN Institute, 2023)
The agro-industrial supply chain is a complex network and involves various parties, from farmers, producers, distributors, to consumers. The use of IoT is expected to increase efficiency, transparency and timeliness in all agro-industrial supply chain processes. This research aims to investigate and analyze the impact of implementing Internet of Things (IoT) technology in agro-industrial supply chain management. This research uses a qualitative approach with descriptive methods. The research results show that the application of the Internet of Things (IoT) in agro-industry, especially in supply chain management, has a significant positive impact. The use of sensors and connected devices enables real-time monitoring of plant conditions, product quality and distribution efficiency. This technology provides the opportunity to manage resources such as water and fertilizer more efficiently, reducing environmental impact and production costs. Additionally, IoT opens up transparency in supply chains, meets consumer demands for more detailed information, and gives supply chain management the ability to respond more quickly to market changes. Thus, the research results confirm that IoT implementation can improve the performance and sustainability of agro-industrial supply chains.